Betty Crocker cookbook : 1500 recipes for the way you cook today. - Crocker, Betty (John Wiley & Sons Inc., 2011)
"This special hardcover keepsake edition of the Betty Crocker Cookbook, 11th edition, contains the entire cookbook, plus a bonus 32-page full-color front section especially for newlyweds"--